Electrocatalytic behaviour of the strontium selenide nanowires for hydrogen evolution reaction at various pH values. (15th August 2022) - Iqbal, Muhammad Faisal; Yang, Yuyang; Li, Guijun; Razaq, Aamir; Zhang, Xincheng; Zhang, Meng
Abstract: Probing the cost-effective electrochemical catalyst is the prerequisite for producing the hydrogen energy through water splitting for commercial considerations. Owing to low cost and greater redox potential, the alkaline metal-based electrochemical catalysts need to be assessed for hydrogen evolution reaction. Herein, the strontium selenide (SrSe) nanowires with various contents of strontium have been synthesized using the hydrothermal process. Sr2 Se1 nanowires attained a good current density at higher pH values and exhibited an over potential of 130 mV at pH of 13.10, with an onset potential of 0.362 V Sr2 Se1 nanowires have also revealed a good Tafel slope of 58 mVdec −1 at pH 13.30, as compared to other catalysts. Moreover, the Sr2 Se1 nanowires have revealed a turn over frequency of 211.50 ms −1  at the fixed reversible electrode potential of 1.0 V and an exchange current density of 6.80 mAcm −2 . The symmetric system, consisting of Sr2 Se1 nanowires, has also revealed a good Tafel slope of 84 mVdec −1 and an over potential of 907 mV at pH of 13.10. The results revealed that the Sr2 Se1 nanowires performed a good hydrogen evolution activity and can be employed as a suitable electrocatalyst. Graphical abstract: Image 1